Relación diámetro – altura total en el crecimiento de las plantas de Ocotea aciphylla (nees) mez en bosque natural y en plantación. Puerto Almendra, Loreto, Perú – 2022 - Huanaquiri Bardales, Reyna Del Pilar (2023)
The study was carried out in Puerto Almendra, San Juan Bautista, Loreto, Peru. The study material was the Ocotea aciphylla (Nees) Mez plants and its objective was to study the relationship diameter - total height of the plants in natural forest and plantation. Two samples (random) were used per condition. In the results, the cubic allometric model was the one that stood out in the relationship for the natural forest with a good degree of relationship; in the plantation the allometric model was S-curve, with an excellent degree of relationship.